Impact of ACE I/D gene polymorphism on congenital renal malformations - Hohenfellner, Katharina; Wingen, Anne-Margret; Nauroth, Oliver; Wühl, Elke; Mehls, Otto; Schaefer, Franz (Pediatric nephrology, 2001)
To investigate the role of the angiotensin converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism on prevalence and progression of disease in children with chronic renal failure (CRF), we determined the ACE I/D genotype in 95 children with CRF due to renal malformations (hypo- /dysplasia, obstructive uropathy, reflux nephropathy; n=59), other congenital or hereditary diseases (n=23), or acquired glomerular disorders (n=13), who had been followed prospectively over a 2-year period. CRF progression rate was followed in each individual by linear regression analysis of estimates of glomerular filtration rate (GFR) obtained every 2 months. Actuarial renal ’survival’ analysis was performed, using a GFR loss of 10 ml/min per 1.73 m2 as a cutoff point. The distribution of the ACE genotype did not differ among the disease groups. There was also no difference in ACE genotype distribution between the patients and a control group of healthy Caucasian children (n=163). Among the children with renal malformations, the 2-year renal survival was significantly lower in those with the DD genotype (61%) than in patients with ID or II genotype (89%, P<0.01). In the other disease groups, the ACE I/D genotype was not predictive of CRF progression. In a multivariate analysis of risk factors, the adverse effect of the DD genotype (risk ratio 10.2, P<0.05) was independent of and additive to those of arterial hypertension (RR 13.2, P<0.001) and gross proteinuria (RR 4.7, P<0.05). We conclude that the ACE DD genotype is a significant risk factor for children with congenital renal malformations to develop progressive CRF. The effect of the ACE polymorphism in this patient group is independent of hypertension and proteinuria.